Improving Usability And Navigation Of Sarawak Public Agencies Websites - Syahrul Nizam, Junaini (Universiti Malaysia Sarawak (UNIMAS), 2004)
With the development of Internet and online services, the importance of usability should be the main concern in designing Sarawak Public Agency websites. This paper will highlight the basic of usability that determines site effectiveness. The speaker will present a theoretical framework that emphasizes on the importance of this attribute to attract web users. Suggestions for design and development of better user-focused websites will also be stressed during the talk.